2015
DOI: 10.1248/bpb.b15-00048
|View full text |Cite
|
Sign up to set email alerts
|

The 5-Lipoxygenase Inhibitor Zileuton Confers Neuroprotection against Glutamate Oxidative Damage by Inhibiting Ferroptosis

Abstract: 5-Lipoxygenase (5-LOX) inhibitors have been shown to be protective in several neurodegenerative disease models; however, the underlying mechanisms remain unclear. We investigated whether 5-LOX inhibitor zileuton conferred direct neuroprotection against glutamate oxidative toxicity by inhibiting ferroptosis, a newly identified iron-dependent programmed cell death. Treatment of HT22 mouse neuronal cell line with glutamate resulted in significant cell death, which was inhibited by zileuton in a dose-dependent man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(94 citation statements)
references
References 28 publications
9
85
0
Order By: Relevance
“…In contrast, suppression of ERK activation using a specific inhibitor U0126 was not able to alter Lox expression, but decreased Alox5 phosphorylation at serine 663 residue (Figure 4D). And in line with previous investigations(14,30), ERK blockade by U0126 or inhibition of Alox5 by Zileuton obviously inhibited ferroptosis process and abrogated neuronal impairment induced by glutamate (Figure 4EandFigure 4F). Similarly, suppression of phosphorylated ERK by U0126 could also inhibited erastin-induced neuronal ferroptosis in HT22 cells while treatment with either a p38 protein kinase inhibitor (SB202190) or a JNK protein kinase inhibitor (SP600125) did not protect neurons from cell death (Supplementary…”
supporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, suppression of ERK activation using a specific inhibitor U0126 was not able to alter Lox expression, but decreased Alox5 phosphorylation at serine 663 residue (Figure 4D). And in line with previous investigations(14,30), ERK blockade by U0126 or inhibition of Alox5 by Zileuton obviously inhibited ferroptosis process and abrogated neuronal impairment induced by glutamate (Figure 4EandFigure 4F). Similarly, suppression of phosphorylated ERK by U0126 could also inhibited erastin-induced neuronal ferroptosis in HT22 cells while treatment with either a p38 protein kinase inhibitor (SB202190) or a JNK protein kinase inhibitor (SP600125) did not protect neurons from cell death (Supplementary…”
supporting
confidence: 92%
“…Lipid peroxidation is a critical feature in the ferroptosis execution. There is ample evidence supporting that various modulators of lipid metabolism including Acyl-CoA synthetase long-chain family 4 (ACSL4), glutathione peroxidase 4 (GPX4), 5-lipoxygenase (Alox5), Alox12 and phosphatidyletha-nolamine-binding protein 1 (PEBP1) are involved in ferroptotic cell death (12)(13)(14)(15)(16). For instance, it has demonstrated that an enhanced Alox5 activity has been found in ferroptosis process under glutamate-triggered neurotoxicity in hippocampal neurons and pharmacological inhibition of Alox5 by Zileuton counteracts ferroptotic death event in this model (14).…”
Section: Introductionmentioning
confidence: 99%
“…We also found E− larvae had increased levels of glutamate (p< 0.001; Supplementary Table 1) relative to E+ larvae, which could signify glutamate toxicity, another metabolic perturbation associated with ferroptosis [53] via inhibition of the cellular cysteine/glutamate antiporter system X c - [51]. Excessive glutamate is neurotoxic [58] and may be a consequence of compromised mitochondria [59]; additional experiments regarding the regulation of neuronal intracellular glutamate levels are required to determine whether these mechanisms also apply to our VitE deficiency model.…”
Section: Discussionmentioning
confidence: 99%
“…A unifying mechanism potentially linking developmental VitE deficiency with many of the metabolic perturbations reported herein – all of which may perturb brain function – is ferroptosis, a process of non-apoptotic programmed cell death [51] that involves several key features observed in our E− larvae, most critically: 1) enhanced enzymatic lipid peroxidation [52], especially due to excessive ARA metabolism via 5- [53] and 15-lipooxygenase [54] activities (Figure 6A-B; including 5- and 15-HETE; 5-oxo-ETE [55]); 2) glutathione depletion [56] (Figure 7); and 3) mitochondrial dysfunction [57] (Figure 10). We also found E− larvae had increased levels of glutamate (p< 0.001; Supplementary Table 1) relative to E+ larvae, which could signify glutamate toxicity, another metabolic perturbation associated with ferroptosis [53] via inhibition of the cellular cysteine/glutamate antiporter system X c - [51].…”
Section: Discussionmentioning
confidence: 99%
“…Zileuton provided significant protection from glutamate-and erastin-induced ferroptosis in HT22 cells (a mouse hippocampal cell line) by inhibition of cytosolic ROS production. 41 …”
Section: Inhibitormentioning
confidence: 99%